Evaluation of leukocyte esterase reagent strip test for rapid bedside diagnosis of spontaneous bacterial peritonitis - Khanal, Kiran Kumar; Khanal, Ajit; Shrestha, Ramila; Thapa, Bhawesh; Baral, Ram Krishna (Nepal Medical College Journal, 2023)
Spontaneous bacterial peritonitis (SBP) is a common complication of cirrhosis with high morbidity and mortality. Early diagnosis and treatment improve survival. Diagnosis is made by ascitic fluid Polymorphoneuclear leukocytes (PMNL) count of >250/mm3 which takes hours and may not be available in rural settings. Leukocyte esterase reagent strips (LERS) test have shown high sensitivity, specificity, and negative predictive value in the diagnosis of SBP. This study was conducted to find the utility of the LERS test for the diagnosis of SBP. This was a prospective hospital-based study conducted at the National Academy of Medical Sciences, Bir Hospital, Nepal. LERS test was performed on ascitic fluid from 140 cirrhotic patients. Colorimetric grading was compared with PMNL count for diagnosing SBP. Sensitivity, specificity, positive predictive value (PPV), negative predictive value (NPV), and accuracy for diagnosing SBP calculated for grade 3 and grade 4 as cut-offs. Among 140 patients, SBP was diagnosed in 27. Grade 3 as cut-off, sensitivity, specificity, PPV, and NPV for the LERS test were 96.3, 90.2, 70.3, and 99 percent respectively. For grade 4 as cut-off, sensitivity, specificity, PPV, and NPV were 81.5, 99.1, 95.6, and 95.7 percent respectively. Accuracy were 91.4 and 95.2 percent for grade 3 and 4 as cut-off respectively. LERS test has shown high sensitivity, specificity, and negative predictive value for the diagnosis of SBP in cirrhotic ascitis. Being simple, rapid, and cost-effective, it can be useful at bedside to start early antibiotic therapy before availability of the PMNL count report.